2007
DOI: 10.1007/s11837-007-0084-6
|View full text |Cite
|
Sign up to set email alerts
|

The development of the COST 531 lead-free solders thermodynamic database

Abstract: Overview Lead-Free SolderThe methods for modeling the thermodynamic properties of multicomponent systems are described in this article. The rules for creating a consistent database for muticomponent systems are described in general terms and documented in relation to the thermodynamic database for lead-free solders, developed within the scope

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 30 publications
0
65
0
1
Order By: Relevance
“…The parameters of the Gibbs energy of metals and the interaction parameters of the liquid and solid phases were taken from the COST531 ver. 3.1 data base [7]. In this database the assessment of the Bi-Zn system was based on Malakhov's system optimization [20] with an improvement of the new data for the solubility of Bi in the hcp-Zn terminal phase [21].…”
Section: Thermodynamic Modellingmentioning
confidence: 99%
See 3 more Smart Citations
“…The parameters of the Gibbs energy of metals and the interaction parameters of the liquid and solid phases were taken from the COST531 ver. 3.1 data base [7]. In this database the assessment of the Bi-Zn system was based on Malakhov's system optimization [20] with an improvement of the new data for the solubility of Bi in the hcp-Zn terminal phase [21].…”
Section: Thermodynamic Modellingmentioning
confidence: 99%
“…The thermodynamic modelling of Lee et al [22], with some amendments of the In-Zn interaction parameters of the binary solid phases, was adopted for the In-Zn system. According to the assessment of Vizdal et al [21], the datasets for the Bi-Sn and Bi-Sn-Zn systems were included in the COST531 database [7].…”
Section: Thermodynamic Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ag-Sb, Ag-Sn, and Sb-Sn binary systems have already been thermodynamically assessed. 3 As far as the ternary system is concerned, literature data for the Ag-Sb-Sn system are rather scarce. However, all authors agree that no ternary intermetallic compounds were observed in the Ag-Sb-Sn system.…”
Section: Introductionmentioning
confidence: 99%